2022
DOI: 10.1039/d2tb00375a
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assemblies of histidine-containing peptides with switchable hydrolase and peroxidase activities through Cu(ii) binding and co-assembling

Abstract: Modulating enzyme activities or functionalities is one of the primary features of biological systems, which is, however, a great challenge for artificial enzyme systems. In this work, we designed and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…For instance, Zn(II)-coordinated peptide/F amyloid assemblies, featuring supramolecular cross-β-sheet secondary structures stabilized by hydrogen bonds, have been shown to exhibit carbonic anhydrase-like catalytic activity for ester bond hydrolysis [ 246 , 247 , 248 ]. Zhang et al demonstrated switchable hydrolase and horseradish peroxidase (HRP)-like activities of supramolecular assemblies of histidine-containing peptides through Cu(II) binding and co-assembly [ 249 ]. Liu et al reported that amyloid-like phenylalanine-Cu(II) fibrils displayed laccase-like catalytic ability and enabled the colorimetric detection of dopamine [ 250 ].…”
Section: Colorimetric Methodsmentioning
confidence: 99%
“…For instance, Zn(II)-coordinated peptide/F amyloid assemblies, featuring supramolecular cross-β-sheet secondary structures stabilized by hydrogen bonds, have been shown to exhibit carbonic anhydrase-like catalytic activity for ester bond hydrolysis [ 246 , 247 , 248 ]. Zhang et al demonstrated switchable hydrolase and horseradish peroxidase (HRP)-like activities of supramolecular assemblies of histidine-containing peptides through Cu(II) binding and co-assembly [ 249 ]. Liu et al reported that amyloid-like phenylalanine-Cu(II) fibrils displayed laccase-like catalytic ability and enabled the colorimetric detection of dopamine [ 250 ].…”
Section: Colorimetric Methodsmentioning
confidence: 99%
“…It has been successfully used for the degradation of chlorophenol and bisphenol and the determination of epinephrine by a smart phone. Zhang et al prepared various self-assembles with histidine-containing peptides as the precursors [ 71 ]. The peptide conformation changed from random coil to β-sheet structure and nanotube with hydrolase activity.…”
Section: Colorimetric Biosensorsmentioning
confidence: 99%
“…Meanwhile, a large amout of nanomaterials have been proposed/developed as promising antibacterial agents, such as silver nanomaterials, 7 copper nanomaterials, 8 oxides, 9 and metal disulfide 10,11 owing to the rapid development of nanotechnology. However, these nanomaterials have achieved limited success in anti-biofilms, primarily due to their insufficient catalytic activities.…”
Section: Introductionmentioning
confidence: 99%